Obesity in Peru - Pajuelo Ramírez, Jaime (2017)
Obesity is a chronic disease presenting in all population groups and with a tendency to a time-driven increase. The highest prevalence occurs in the adult population followed by the school, pre-school and adolescent group. Those living in urban areas, women and those not considered as poor are the most affected. Obesity is already present throughout the world and has been declared the epidemic of the 21st century. Its presence is related to diseases such as diabetes mellitus 2, hypertension, dyslipidemias and some types of cancer. Complications such as insulin resistance and metabolic syndrome are already present in adolescents. Factors that condition changes in lifestyles (dietary patterns and sedentary lifestyle) are increasingly prevalent and with a trend for more presence in the future, which makes the obesity panorama look bleak. Despite all the recommendations made by international organizations, in particular the World Health Organization (WHO), and the measures taken by the Peruvian state, especially the law on the promotion of healthy eating for children and adolescents, the prevalence of obesity continues to rise. It is necessary to raise awareness among the population that obesity is a disease that leads to many complications that seriously compromise health. It is necessary to follow the recommendations to a healthy diet and promotion of physical activity, and commit people and institutions to a healthy lifestyle, in an effort to provide good health to the population.